2003
DOI: 10.1111/j.1534-6935.2003.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis in dogs

Abstract: Objective: To summarize current information regarding severity assessment, diagnostic imaging, and treatment of human and canine acute pancreatitis (AP). Human-based studies: In humans, scoring systems, advanced imaging methods, and serum markers are used to assess the severity of disease, which allows for optimization of patient management. The extent of pancreatic necrosis and the presence of infected pancreatic necrosis are the most important factors determining the development of multiple organ failure (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 111 publications
(325 reference statements)
0
26
0
Order By: Relevance
“…As pulmonary interstitial pressure increases into the positive pressure range and the lymphatics are unable to remove this fluid, it leaks into the alveolar space. 33 In a prospective observational study of human septic patients, a positive cumulative fluid balance had a significant negative influence on survival. Experiments performed on dogs showed that pulmonary capillary pressure must increase to a value at least equal to the COP of the plasma inside the capillaries before clinically relevant pulmonary edema occurs.…”
Section: Pulmonary Edemamentioning
confidence: 99%
“…As pulmonary interstitial pressure increases into the positive pressure range and the lymphatics are unable to remove this fluid, it leaks into the alveolar space. 33 In a prospective observational study of human septic patients, a positive cumulative fluid balance had a significant negative influence on survival. Experiments performed on dogs showed that pulmonary capillary pressure must increase to a value at least equal to the COP of the plasma inside the capillaries before clinically relevant pulmonary edema occurs.…”
Section: Pulmonary Edemamentioning
confidence: 99%
“…However, the true incidence of the disease is unknown as some dogs may have subclinical signs or mild disease 5 . Acute pancreatitis, once diagnosed, has a reported mortality rate ranging from 27% to 42% although most dogs with mild clinical symptoms recover without complications 6 …”
Section: Introductionmentioning
confidence: 99%
“…In humans, delayed surgical intervention has been reported to decrease morbidity and mortality in these cases 8,21 . While no specific guidelines have been established, currently accepted criteria for surgical intervention in dogs include evidence of infection, local complications (abscessation or biliary obstruction), diagnostic confirmation (of neoplastic versus nonneoplastic disease), persistent distant organ complications, and failure to respond to aggressive medical management 22–24 …”
Section: Introductionmentioning
confidence: 99%